Biopsychosocial Correlates of Binge Eating Disorder in Caucasian and African American Women with Obesity in Primary Care Settings. (7th December 2015) - Udo, Tomoko; White, Marney A.; Lydecker, Janet L.; Barnes, Rachel D.; Genao, Inginia; Garcia, Rina; Masheb, Robin M.; Grilo, Carlos M.
Abstract: This study examined racial differences in eating‐disorder psychopathology, eating/weight‐related histories, and biopsychosocial correlates in women ( n  = 53 Caucasian and n  = 56 African American) with comorbid binge eating disorder (BED) and obesity seeking treatment in primary care settings. Caucasians reported significantly earlier onset of binge eating, dieting, and overweight, and greater number of times dieting than African American. The rate of metabolic syndrome did not differ by race. Caucasians had significantly elevated triglycerides whereas African Americans showed poorer glycaemic control (higher glycated haemoglobin A1c [HbA1c]), and significantly higher diastolic blood pressure. There were no significant racial differences in features of eating disorders, depressive symptoms, or mental and physical health functioning. The clinical presentation of eating‐disorder psychopathology and associated psychosocial functioning differed little by race among obese women with BED seeking treatment in primary care settings. Clinicians should assess for and institute appropriate interventions for comorbid BED and obesity in both African American and Caucasian patients. Copyright © 2015 John Wiley & Sons, Ltd and Eating Disorders Association.